Pengaruh Penerapan Green Accounting Dan Kinerja Lingkungan Terhadap Kinerja Keuangan Perusahaan - Ros Juliana Lubis; Tiara Hutapea; Arnol Siagian; Bonaraja Purba (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This paper aims to explore the impact of the implementation of green accounting and environmental performance on the financial performance of companies, with a specific focus on the mining and manufacturing sectors in Indonesia. The study delves into the challenges of environmental pollution and the necessity for companies to enhance profitability while improving financial performance. The research assesses the relationship between green accounting, environmental performance, and financial outcomes, aiming to provide insights into whether companies applying green accounting can enhance profitability through good environmental performance.